Effects of Nanographene Addition on Tensile and Electrical Properties of Nylon 6,6 Nanocomposite - Abdullah Sani, Nurhernida; Abd Manaf, Mohd Edeerozey; Mohamad, Noraiham; Shueb, Mohamad Iqbal (Universiti Teknikal Malaysia Melaka, 2017)
The effects of nanographene (NG) filler on tensile and electrical properties of nylon 6,6 nanocomposite were analyzed. The samples were fabricated by blending nylon 6,6/NG in Sino compounder twin screw machine which subsequently injected into standard size specimens for tensile and electrical conductivity test. An addition of small percentages of NG filler, i.e., 0.3, 0.5 and 1.0 wt% significantly affected the tensile performance and electrical conductivity of nylon 6,6 nanocomposite, in which tensile properties and electric conductivity improved with increasing nanographene filler loading.